IMPLEMENTATION OF ELECTRONIC GOVERNMENT IN SUMEDANG REGENCY - Herman Suryatman; Ella Lesmanawaty Wargadinata (Jurnal Ilmu Pemerintahan Widya Praja, 2024)
This research was aimed at providing a detailed overview of the current e-government implementation in Sumedang Regency, developing scenarios and alternatives for sustainable e-government implementation, assessing its roles in enhancing community welfare by 2030 and formulating e-government strategies for the next six years based on constructed scenarios. Qualitative methods, specifically exploratory descriptive research using scenario planning analysis by Woody Wade were employed. Data analysis utilized the SOAR tool framework. The research results showed that first, the future of e-government in Sumedang Regency hinges on two dimensions: Digital leadership and digital literacy. Second, there are four developed scenarios for e-government implementation: Cloudy, Bright, Storm, and Rain. The first scenario was the Cloudy scenario, which is a scenario in which the digital leadership of regional leaders in Sumedang Regency is strong, but the digital literacy of state officials and citizens is low. The second is the Bright Scenario, a scenario in which the digital leadership of regional leaders in Sumedang Regency is strong and the digital literacy of state officials and citizens is high. The third is the Storm Scenario, a scenario in which the digital leadership of regional leaders in Sumedang Regency is weak and the digital literacy of state officials and citizens is low. The fourth, is the Rain Scenario, a scenario in which the digital leadership of regional leaders in Sumedang Regency is weak, but the digital literacy of state officials and citizens is high.Keywords: E-Government; Digital Leadership; Digital Literacy; Scenario Planning